The metabolic costs of gardening tasks in children - Park, Sin-Ae; Lee, Ho-Sang; Lee, Kwan-Suk; Son, Ki-Cheol; Shoemaker, Candice A. (My University, 2014)
The metabolic cost of 10 gardening tasks was measured in children to determine the exercise intensities associated with these tasks. Seventeen children [(mean ± SD) aged 12.4 ± 0.7 years and body mass index 21.6 ± 4.0 kg·mˉ²] participated in this study. The children performed the 10 gardening tasks at a garden previously established in Cheongju, Chungbuk, South Korea. They visited the garden twice and performed five different tasks on each visit. Five minutes were provided to complete each gardening task and a 5-minute rest was allowed between each task. The children wore a portable telemetric calorimeter and a heart rate monitor for measurement of oxygen uptake and heart rate during the gardening tasks. The results show that the 10 gardening tasks represented moderate- to high-intensity physical activity for the children [4.3 ± 0.5 to 6.6 ± 1.6 metabolic equivalents (MET)]. Digging (6.6 ± 1.6 MET) and raking (6.2 ± 1.5 MET) were high-intensity physical activities, and digging was more intense than the other gardening tasks performed in this study (P < 0.05). Tasks such as weeding (5.8 ± 1.1 MET), mulching (5.5 ± 1.3 MET), hoeing (5.3 ± 0.7 MET), sowing seeds (5.0 ± 1.1 MET), harvesting (4.8 ± 0.6 MET), watering (4.6 ± 1.1 MET), mixing growing medium (4.4 ± 0.6 MET), and planting transplants (4.3 ± 0.5 MET) were moderate-intensity physical activities. The MET data for the gardening tasks will facilitate the development of garden-based exercise interventions for children, which can promote health and physically active lifestyle.
Keywords: Horticultural therapy; Physical activity; Socio-horticulture; Children; Metabolic cost; Gardening